IMPROVEMENT OF REGIONAL AND MUNICIPAL FINANCE MANAGEMENT AS A FACTOR OF ADVANCEMENT OF INTERBUDGET RELATIONS - Alexandrovich , Vladimir; Kolesov, Roman; Burykin, Alexey; Yurchenko, Alexander; Biryukov, Vladimir (Revista Inclusiones, 2020)
The paper is concerned with the development of approaches to improve regional and municipal finance management as a factor in the advancement of interbudget relations in Russia. It is established that efforts to improve the mechanisms of regional and municipal finance management are now one of the priorities in state policies aimed at ensuring stable, dynamic and balanced development of the national economy. It is shown that the advancement of interbudget relations is concerned with building up the potential to bring down fiscal capability differentiations between the subjects and municipalities of the country, their capacity to pursue balanced budgets, administer their competences and provide equal opportunities for the public in obtaining budget services at or above the minimum quality and quantitative levels required to meet constitutional guarantees.